PENGARUH MODEL PEMBELAJARAN INQUIRY DENGAN PENDEKATAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) TERHADAP HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR KELURAHAN CIPETE SELATAN - Ananda Salsabillah Zahra; Tunjungsari Sekaringtyas; Prayuningtyas Angger Wardhani (STKIP Subang, 2026)
Elementary school is the first stage of formal education that plays a crucial role in developing children's foundational knowledge and skills. At this level, students are introduced to fundamental concepts across various subjects, including Science, which fosters structured thinking skills. However, science in elementary schools still faces several challenges, such as low student learning outcomes and limited learning resources to support the instructional process. The Inquiry Learning model can enhance students' active participation in discovering concepts, but its implementation requires technological support to optimize the inquiry process. This study aimed to determine the effect of the Inquiry Learning model integrated with the Technological Pedagogical Content Knowledge (TPACK) approach on students' learning outcomes in the food chain topic. The study employed a quasi-experimental method using a pretest-posttest control group design. The sample consisted of 60 students, with 30 students in the experimental class and 30 students in the control class. Learning outcome data were collected through pretests and posttests and analyzed using an Independent t-test. The results showed a two-tailed significance value of 0.01 (α < 0.05), indicating that the Inquiry Learning model integrated with the TPACK approach had a significant effect on students' learning outcomes in the food chain topic. The implementation of all Inquiry Learning phases supported by digital media enhanced students' engagement in learning and helped them develop a more meaningful understanding of the concepts.